Mesoporous TUD-1 supported indium oxide nanoparticles for epoxidation of styrene using molecular O-2 - Rahman, Sumbul; Farooqui, Saleem A.; Rai, Aditya; Kumar, Rawesh; Santra, Chiranjit; Prabhakaran, Vinod C.; Bhadu, Gopala Ram; Sen, Debasis; Mazumder, S.; Maity, Sudip; Sinha, Anil K.; Chowdhury, Biswajit (RSC Advances, 2015)
Activation of molecular O-2 by metal or metal oxide nanoparticles is an area of recent research interest. In this work, for the first time, we report that indium oxide nanoparticles of <3 nm size dispersed on mesoporous silica (TUD-1) can activate molecular O-2 and produce styrene epoxide with a selectivity of 60% and styrene conversion around 25% under mild conditions. It is found that neither indium oxide nor TUD-1 themselves respond to the styrene epoxidation reaction. The computational studies provide evidence that an oxygen molecule is highly polarized when it is located near the interface of both surfaces. The kinetic study shows that the reaction is of pseudo-first order and that the activation energy for styrene conversion is 12.138 kJ mol(-1). The catalysts are recyclable for up to four regeneration steps, with the styrene conversion and styrene epoxide selectivity almost unchanged.